Analytical electron tomography. (7th July 2016) - Leary, Rowan K.; Midgley, Paul A.
Abstract: Abstract : This article highlights recent advances in analytical electron tomography (AET), the three-dimensional (3D) extension of conventional nanoanalytical techniques, in which electron energy loss, x-ray spectroscopy, and electron diffraction are combined with tomographic acquisition and reconstruction. Examples from the literature illustrate how new 3D information, gleaned from AET, provides insights into not just morphology and composition, but also the electronic, chemical, and optical properties of materials at the nanoscale. We describe how the "multidimensional" nature of AET leads to "big data" sets, how these can be analyzed optimally, and how AET may develop further.